Excision of Nucleopolyhedrovirus Form Transgenic Silkworm Using the CRISPR/Cas9 System - Dong, Zhanqi; Dong, Feifan; Yu, Xinbo; Huang, Liang; Jiang, Yaming; Hu, Zhigang; Chen, Peng; Lu, Cheng; Pan, Minhui (Frontiers in Microbiology, 2018)
Abstract CRISPR/Cas9-mediated genome engineering has been shown to efficiently suppress infection by disrupting genes of the pathogen. We recently constructed transgenic lines expressing CRISPR/Cas9 and the double sgRNA target Bombyx mori nucleopolyhedrovirus (BmNPV) immediate early-1 (ie-1) gene in the silkworm, respectively, and obtained four transgenic hybrid lines by G1 generation hybridization: Cas9(-)/sgRNA(-), Cas9(+)/sgRNA(-), Cas9(-)/sgRNA(+), and Cas9(+)/sgRNA(+). We demonstrated that the Cas9(+)/sgRNA(+) transgenic lines effectively edited the target site of the BmNPV genome, and large fragment deletion was observed after BmNPV infection. Further antiviral analysis the Cas9(+)/sgRNA(+) transgenic lines shows that the median lethal dose (LD50) is 1,000-fold higher than the normal lines after inoculation with occlusion bodies (OB). The analysis of economic characters and off-target efficiency of Cas9(+)/sgRNA(+) transgenic hybrid line showed no significant difference compared with the normal lines. Our findings indicate that CRISPR/Cas9-mediated genome engineering more effectively targets the BmNPV genomes and could be utilized as an insect antiviral treatment.